2011
DOI: 10.1097/hco.0b013e32834938c6
|View full text |Cite
|
Sign up to set email alerts
|

Coronary computed tomography angiography

Abstract: When used appropriately, CCTA has been established as a valid noninvasive imaging alternative to ICA in selected patients at low to intermediate risk of CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Data from the most motion-free phase (diastasis usually occurs in mid-diastole) are then reconstructed for analysis. By contrast, prospective EKG triggering involves axial acquisition (table intermittently advances, usually with each heart beat) with the X-ray tube on during diastasis only [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from the most motion-free phase (diastasis usually occurs in mid-diastole) are then reconstructed for analysis. By contrast, prospective EKG triggering involves axial acquisition (table intermittently advances, usually with each heart beat) with the X-ray tube on during diastasis only [3].…”
Section: Introductionmentioning
confidence: 99%
“…The gold standard is invasive right-heart catheterization, but non-invasive imaging modalities include echocardiography, cardiac magnetic resonance imaging, and cardiac computed tomography (CT) [1,2]. CT coronary angiography (CTCA) uses electrocardiogram-gated image acquisition after contrast administration when a predetermined level of contrast opacification is reached to obtain high-resolution, three-dimensional depictions of both the cardiac structures and the coronary vessels [3]. Depending on the scanner, two acceptable methods exist: automatic bolus tracking or the timing bolus method for determining the contrast transit time.…”
Section: Introductionmentioning
confidence: 99%
“…59 However, the role of calcium scoring alone in ACS risk stratification in the ED continues to be debated. Prior studies have shown that noncalcified plaques are more likely to be present in younger cohorts, [59][60][61] in diabetic patients, 62 and in patients with ACS compared with those with stable CAD. 63 A calcium score of zero may not predict the absence of CAD.…”
Section: Coronary Calcium Scoringmentioning
confidence: 96%
“…Plaque component analysis based on the CT number is becoming popular, but it still needs further validation or improvement to be reliably used as an outcome measure. 29 The strength of this article is that we have a large clinical population that underwent repeat CCTA after a prior CCTA excluding significant stenosis. This is partly because of the high availability of CT devices in Japan with 97.3 scanners per million individuals, 3 times the ratio in the United States.…”
Section: Discussionmentioning
confidence: 99%